RECOGNIZING OBJECTS IN IMAGES USING ARTIFICIAL INTELLIGENCE AND PYTHON - Soliev Bakhromjon Nabijonovich; Ermatova Zarina Kakhramonovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article explores methods and technologies for recognizing objects in images using artificial intelligence (AI) and the Python programming language. We will consider various approaches to solving the problem of object recognition, present a literature review, and offer practical examples of software solutions.